2021
DOI: 10.2174/1573409916666191226110029
|View full text |Cite
|
Sign up to set email alerts
|

Petra/Osiris/Molinspiration and Molecular Docking Analyses of 3-Hydroxy-Indolin-2-one Derivatives as Potential Antiviral Agents

Abstract: Background: Studies on the interaction between bioactive molecules and HIV-1 virus has been the focus of recent research in the scope of medicinal chemistry and pharmacology. Objective: Investigating the structural parameters and physic-chemical properties of elucidating and identifying of the antiviral pharmacophore sites. Method: A mixed computational Petra/Osiris/Molinspiration/DFT (POM/DFT) based model has been developed for the identification of physico-chemical parameters governing the bioactivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…More also, Table 4 shows MLR Y-randomization test, the strength, and consistent of the built model were verified by the coefficient of Y-randomization of 0.6433 shown in Table 4. Interestingly, it was observed that all the validation criteria were fully agreed with the acceptable threshold parameters stated in a literature [36].…”
Section: Table 10 Bioactivity Index and Medicinal Chemistry Accessibi...supporting
confidence: 65%
“…More also, Table 4 shows MLR Y-randomization test, the strength, and consistent of the built model were verified by the coefficient of Y-randomization of 0.6433 shown in Table 4. Interestingly, it was observed that all the validation criteria were fully agreed with the acceptable threshold parameters stated in a literature [36].…”
Section: Table 10 Bioactivity Index and Medicinal Chemistry Accessibi...supporting
confidence: 65%
“…The invention of POM Theory leads us to identify each type of pharmacophore sites with real success, on the basis of semi-empirical data of about 7.000 antibacterial, antifungal, antitumor and antiviral commercial and new drugs. All details of therapeutic applications of POM Theory are given in the literature and the identification of different and various types of pharmacophore sites is well established [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] ,…”
Section: Resultsmentioning
confidence: 99%
“…These rules filter the compounds and make the drug candidates orally available. To analyze the oral bioavailability of the plant-derived compounds, the drug-likeness property of the compounds was predicted through the Molinspiration server [ 52 ].…”
Section: Methodsmentioning
confidence: 99%